Endovascular variable aortic control (EVAC) versus resuscitative endovascular balloon occlusion of the aorta (REBOA) in a swine model of hemorrhage and ischemia reperfusion injury. Issue 3 (September 2018) - Williams, Timothy K.; Tibbits, Emily M.; Hoareau, Guillaume L.; Simon, Meryl A.; Davidson, Anders J.; DeSoucy, Erik S.; Faulconer, E. Robert; Grayson, J. Kevin; Neff, Lucas P.; Johnson, Michael Austin
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is effective at limiting hemorrhage from noncompressible sources and restoring but causes progressive distal ischemia, supraphysiologic pressures, and increased cardiac afterload. Endovascular variable aortic control (EVAC) addresses these limitations, while still controlling hemorrhage. Previous work demonstrated improved outcomes following a 90-minute intervention period in an uncontrolled hemorrhage model. The present study compares automated EVAC to REBOA over an occlusion period reflective of contemporary REBOA usage. METHODS: Following instrumentation, 12 Yorkshire-cross swine underwent controlled 25% hemorrhage, a 45-minute intervention period of EVAC or REBOA, and subsequent resuscitation with whole blood and critical care for the remainder of a 6-hour experiment. Hemodynamics were acquired continuously, and laboratory parameters were assessed at routine intervals. Tissue was collected for histopathologic analysis. RESULTS: No differences were seen in baseline parameters. During intervention, EVAC resulted in more physiologic proximal pressure augmentation compared with REBOA (101 vs. 129 mm Hg; 95% confidence interval [CI], 105–151 mm Hg; p = 0.04). During critical care, EVAC animals required less than half the amount of crystalloid (3, 450 mL; 95% CI, 1, 215–5, 684 mL] vs. 7, 400 mL [95% CI, 6, 148–8, 642 mL]; p < 0.01) and vasopressors (21.5 ng/kg [95% CI, 7.5–35.5 ng/kg] vs. 50.5 ng/kg [95% CI, 40.5–60.5 ng/kg]; p = 0.05) when compared with REBOA animals. Endovascular variable aortic control resulted in lower peak and final lactate levels. Endovascular variable aortic control animals had less aortic hyperemia from reperfusion with aortic flow rates closer to baseline (36 mL/kg per minute [95% CI, 30–44 mL/kg per minute] vs. 51 mL/kg per minute [95% CI, 41–61 mL/kg per minute]; p = 0.01). CONCLUSIONS: For short durations of therapy, EVAC produces superior hemodynamics and less ischemic insult than REBOA in this porcine-controlled hemorrhage model, with improved outcomes during critical care. This study suggests EVAC is a viable strategy for in-hospital management of patients with hemorrhagic shock from noncompressible sources. Survival studies are needed to determine if these early differences persist over time. Abstract : Supplemental digital content is available in the text.